Fabrication of Microporous Water Filter Using Titanium Dioxide Particles, Silica Particles, and Polyethylene Glycol - Aris Priatama; Mikrajuddin Abdullah; Khairurrijal Khairurrijal; Hernawan Mahfudz (Journal of Engineering and Technological Sciences, 2010)
We report the fabrication of microporous filter for use in filtering both inorganic  and  organic  substances  from  liquid  materials.  Titania  (TiO 2)  anatase was  used  as  the  main  material  for  this  filter.  Polyethylene  glycol  (PEG)  with average  molecular  weight  of  20,000  was  also  used  as  additive  to  control  the formation  of  pores,  especially  pore  sizes.  The  mixture  of  titania  and  PEG  was pressed into cylindrical tablet shape at room temperature  and then simply heated inside a furnace up to temperature where the PEG decomposed into gas to leave only connected titania particles. The use of titania as base material for the filter allows  the  organic  substances  that  trapped  inside  the  filter  pores  to  be  easily removed by heating up the used filter at above decomposition temperature of the trapped  organics.  We  also  made  other  filter  by  adding  small  amount  of  silica (SiO2)  particles  to  reduce  the  size  of  the  pores  as  well  as  to  improve  the mechanical  strength.  We  observed  that  filters  containing  silica  particles,  with smaller  in  size  compared  to  titania,  resulted  in  better  mechanical  strength, smaller in pore sizes and better filtering results in term of turbidity and dissolved oxygen (DO) content. This  method is potential for development of larger scale and cheaper water filters for use in various applications.